2015
DOI: 10.3390/nu7095335
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Antioxidant Defense System Using Different Lipid Emulsions in Parenteral Nutrition in Children after Hematopoietic Stem Cell Transplantation

Abstract: Background: Traditionally, lipids used in parenteral nutrition (PN) are based on ω-6 fatty acid-rich vegetable oils, such as soybean oil, with potential adverse effects involving oxidative stress. Methods: We evaluated the antioxidant defense system in children, after hematopoietic stem cell transplantation (HSCT), who were randomized to use a lipid emulsion with fish oil or soybean oil. Blood samples at baseline, at 10 days, and at the end of the PN were taken to analyze plasma retinol, α-tocopherol, β-carote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…20 These first results support current efforts to further investigate the value of EN in large, prospective randomized controlled trials as the ongoing study authored by Lemal et al 51 Current literature also questions the role of antioxidants, mainly glutamine, vitamins, trace elements and immunomudulants, for example, omega 3 fatty acids. [52][53][54][55][56] Except for vitamin D, there is no proven benefit of those substances. 57,58 Unfortunately, there were no studies of high quality to integrate into this review.…”
Section: Discussionmentioning
confidence: 99%
“…20 These first results support current efforts to further investigate the value of EN in large, prospective randomized controlled trials as the ongoing study authored by Lemal et al 51 Current literature also questions the role of antioxidants, mainly glutamine, vitamins, trace elements and immunomudulants, for example, omega 3 fatty acids. [52][53][54][55][56] Except for vitamin D, there is no proven benefit of those substances. 57,58 Unfortunately, there were no studies of high quality to integrate into this review.…”
Section: Discussionmentioning
confidence: 99%
“…Today, at least a third of EBMT centers uses glutamine as an oral supplement and/or added to PN. However, more recent studies question the role of this antioxidant and other immune-nutrients [49][50][51]. Owing to the lack of proven benefit, the use of these substances should not be recommended anymore.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the in vivo studies addressing the issue of beneficial or adverse effects of FO-based nutrition mixtures were performed on a short-term (up to 14 days) basis. As far as oxidative stress is concerned, no effect of FO-based emulsions was reported in six studies [9][10][11][12][13][14] while their anti-oxidative effect was found in two studies [15,16]. One human study reported the pro-oxidative effect of FO emulsions [17].…”
Section: Introductionmentioning
confidence: 99%